2022
DOI: 10.1109/tsc.2020.3005347
|View full text |Cite
|
Sign up to set email alerts
|

epcAware: A Game-Based, Energy, Performance and Cost-Efficient Resource Management Technique for Multi-Access Edge Computing

Abstract: The Internet of Things (IoT) is producing an extraordinary volume of data daily, and it is possible that the data may become useless while on its way to the cloud for analysis, due to longer distances and delays. Fog/edge computing is a new model for analyzing and acting on time-sensitive data (real-time applications) at the network edge, adjacent to where it is produced. The model sends only selected data to the cloud for analysis and long-term storage. Furthermore, cloud services provided by large companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…2) Resource allocation in edge and fog computing systems: This section is devoted to the research works addressing services consisting of multiple components, such as VMs, containers or tasks, but there is no relation among the constituent elements taken into account. Following our Platform components dimension, the underlying infrastructure, where the service components are mapped to, can be multi-edge [80], [95], [129], [131]- [133], [135], [137], [140], [169], [180], [182], cloud-edge [59], [64], [68], [70], [75], [127], [161], [170], [174], [176], [178] or multi-cloud [51] but the core problem to be tackled, i.e., component placement, is similar.…”
Section: B Multiple Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…2) Resource allocation in edge and fog computing systems: This section is devoted to the research works addressing services consisting of multiple components, such as VMs, containers or tasks, but there is no relation among the constituent elements taken into account. Following our Platform components dimension, the underlying infrastructure, where the service components are mapped to, can be multi-edge [80], [95], [129], [131]- [133], [135], [137], [140], [169], [180], [182], cloud-edge [59], [64], [68], [70], [75], [127], [161], [170], [174], [176], [178] or multi-cloud [51] but the core problem to be tackled, i.e., component placement, is similar.…”
Section: B Multiple Componentsmentioning
confidence: 99%
“…The authors define a link-path formalization along with a heuristic approach for the placement of virtualization infrastructure resources and user assignments, i.e., determining where to install cloudlet facilities among sites, and assign access points, such as base stations, to them. In a similar vein, researchers in [75] suggest game-theoretic techniques for VM placement to ensure application's performance while they aim to jointly minimize infrastructure energy consumption and cost. Dedicated telco use cases are addressed with similar objectives, where the management cost of Telecom infrastructure vendors' network [170] and the 5G infrastructure [95] is to be optimized.…”
Section: B Multiple Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the prediction results, a mobile data offloading strategy based on cross-entropy is proposed to maximize the system throughput by determining which users to be offloaded to Wi-Fi systems. Z. Muhammad et al [29] suggested game-theoretic resource management techniques to minimize infrastructure energy consumption and costs while meeting QoS of users. B. Ali et al proposed [30] a Volunteer Supported Fog Computing (VSFC) that tries to explore the interplay of these two distributed computing domains and targets to reduce inherent communication delays of cloud computing, energy consumption, and network usage.…”
Section: A Energy-aware Edge Computingmentioning
confidence: 99%